Life abroad Effects, problems and ways of coping of selected Overseas Filipina Workers (OFW). - Alura, Sherna C.; Daban, Virginia C. (Sherna C. Alura, 2009)
This paper is a study on the effects, problems and ways of coping of Overseas Filipina Workers. It aimed to find out particular effects of working abroad to the OFW herself, particular problems they have encountered and their ways of coping.